2004
DOI: 10.1111/j.0022-1112.2004.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic relationships within the Mediterranean turbot inferred by mitochondrial DNA haplotype variation

Abstract: The Mediterranean turbot Psetta maxima consists of two main genetically distinct lineages (western Mediterranean and 'eastern secluded Mediterranean' basins) as investigated by mitochondrial DNA analysis. Within the latter lineage, most haplotypes from the Sea of Azov were endemic and more than half of them derived from a single ancestral haplotype shared among all the eastern Mediterranean areas. There was no relation between morphotype variation in bony tubercles and mitochondrial genealogy. # 2004 The Fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,340 publications
(33 citation statements)
references
References 9 publications
5
25
3
Order By: Relevance
“…the determined Kimura 2-parameter /K2P/ interhaplotype genetic distances ranged from zero to 0.017 (Se = 0.007), with an average value equal to 0.008 (Se = 0.002). the maximum and average values of the K2P genetic distance calculated for the studied haplotypes were significantly lower than those for the 'Pmax' set of turbot cR haplotypes reported by Suzuki et al (16), (K2P max = 0.044, Se = 0.011; K2P avr = 0.014, Se = 0.003). the 'Pmax' set resembles turbot samples collected from a geographically broader area including the Atlantic ocean, western and eastern Mediterranean and related seas.…”
Section: Resultscontrasting
confidence: 75%
See 4 more Smart Citations
“…the determined Kimura 2-parameter /K2P/ interhaplotype genetic distances ranged from zero to 0.017 (Se = 0.007), with an average value equal to 0.008 (Se = 0.002). the maximum and average values of the K2P genetic distance calculated for the studied haplotypes were significantly lower than those for the 'Pmax' set of turbot cR haplotypes reported by Suzuki et al (16), (K2P max = 0.044, Se = 0.011; K2P avr = 0.014, Se = 0.003). the 'Pmax' set resembles turbot samples collected from a geographically broader area including the Atlantic ocean, western and eastern Mediterranean and related seas.…”
Section: Resultscontrasting
confidence: 75%
“…Dover sole (15), Japanese flounder (6) and willowy flounder (21). Despite the observed very low interhaplotype genetic distance the present study showed a high level of haplotype diversity with an average value of 0.47 (36 haplotypes for 76 analyzed samples) versus 0.42 (28 haplotypes for 66 turbot samples) for the Pmax haplotypes, Suzuki et al (16). the main reason is that the majority of the identified haplotypes originate from a small set of dominant haplotypes following single nucleotide substitution.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations